Maritime economics management and marketing - Branch, Alan E. (Routledge/Taylor & Francis Group, 2016)
Extensively updated and revised, this third edition explains in simple terms the practical economic considerations involved in modern shipping management in changing legal and logistical environments - primarily marketing-driven - in the liner-cargo, bulk-cargo and specialized-tonnage markets.